2020
DOI: 10.1007/s00508-020-01723-9
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of coronavirus disease 2019 (COVID-19) in Austria

Abstract: This is a report on the first identified cases of coronavirus disease 2019 (COVID-19) in Austria. The first documented case was a person who stayed in Kühtai, Tyrol, from 24 to 26 January 2020, and had been infected by a Chinese instructor in Starnberg (Germany) between 20 and 22 January. This counts as a German case since her diagnosis was eventually made in Munich (Germany) on 28 January. On 25 February, two cases imported from Italy were diagnosed in Innsbruck but again no secondary cases were identified in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 18 publications
0
50
0
4
Order By: Relevance
“…Among these cases was CeMM1056 (node N13), who further transmitted the virus to case CeMM1057 (node N15) as previously described for the 20,457 mutation linking cluster A and AL ( Fig. 4E) (17). Based on these data, we investigated the transmission dynamics between known pairs of donors and recipients by inferring the number of virions initiating the infection, also known as the genetic bottleneck size (22,24).…”
Section: Impact Of Transmission Bottlenecks and Intra-host Evolution mentioning
confidence: 85%
See 2 more Smart Citations
“…Among these cases was CeMM1056 (node N13), who further transmitted the virus to case CeMM1057 (node N15) as previously described for the 20,457 mutation linking cluster A and AL ( Fig. 4E) (17). Based on these data, we investigated the transmission dynamics between known pairs of donors and recipients by inferring the number of virions initiating the infection, also known as the genetic bottleneck size (22,24).…”
Section: Impact Of Transmission Bottlenecks and Intra-host Evolution mentioning
confidence: 85%
“…As of August 7, 2020, contact tracing had been performed for all 21,821 reported SARS-CoV-2 positive cases. Out of these, 10,385 cases were linked to epidemiological clusters, whereas no infection chains were identified for the remaining cases (17). Linked to Austria's prominent role in international winter tourism, the country emerged as a potential superspreading transmission hub across the European continent in early 2020.…”
Section: Coronavirusmentioning
confidence: 99%
See 1 more Smart Citation
“…We specifically asked the participants in our study about staying in geographic regions and places with high COVID-19 activity. Interestingly, stay in an Austrian ski resort where at least one COVID-19 superspreading event had occurred in February/March 2020 was indeed an independent risk factor for seropositivity 21 . Several studies have by now identified an association between the AB0 blood group system and acquisition of COVID-19.…”
Section: An Important Finding Of Our Study Is That Participants Livinmentioning
confidence: 99%
“…Extensive prior preparation was not possible. The close geographical proximity to one of Germany's rst SARS-CoV-2 hotspots in the Heinsberg area on top of numerous travel returners from the Alpine region, led to maxed-out capacity (2,3). In addition, a large number of UHC employees with a relevant travel history or contact with SARS-CoV-2 positive patients had to be tested to avoid further spread of the disease within the hospital system (4,5).…”
Section: Introductionmentioning
confidence: 99%